Analyzing Top-Level Athletes’ Activities to Identify Their Transversal Competencies for Career Transition - Laurène Houtin; Clémence Brun; Marine Masetto; Alexis Akinyemi (SAGE Open)
Because of a lack of performance or their age, top-level athletes often have to rebuild their professional future outside the sports sector and without any substantial diploma. The experiences and activities of this population may differ greatly from those of regular career transition-seeking people. Therefore, understanding these specificities and identifying the transversal competencies of top-level athletes is a challenge if we are to provide efficient career guidance for their transition. To do this, 43 top-level athletes underwent semistructured interviews. A content analysis highlighted 15 themes and 240 transversal activities of the interviewed top-level athletes, showing that it is possible to identify transversal activities in the daily lives of top-level athletes that match other careers. This allowed us to create a matrix able to join the activities and regular occupations listed in the ROME job directory of France Labor. We discuss the implications of these results for initiatives such as digital career guidance tools.